(untitled) (Maslahah: Journal of Islamic Studies, 2024)
Trade transactions nowadays are experiencing very rapid development. It’s natural that in the process of its development, many problems arise along with ways to overcome them. Salah satu masalah utama adalah kesenjangan risiko antara ekspor dan impor. To reduce this risk, banks often use Letters of Credit (L/C) as the primary financing method. L/C is a risk-free financing method that allows exports and imports to be financed by the bank. However, the L/C transaction mechanism, which involves the issuing bank negotiating with the importer, does not comply with Sharia principles. The high costs of L/C transactions and the lack of transparency in the bank’s role in providing financial support for imports without deposits in the bank are issues that contradict Sharia principles. Untuk mengatasi masalah ini dan memenuhi kebutuhan prinsip-prinsip Syariah dalam bisnis, bank sering menggunakan L/C di lembaga keuangan berbasis Syariah, seperti L/C impor dan ekspor berbasis Syariah.